Posisi Teologis al-Dāruquṭnī Terkait Hadis-Hadis Sifat: Analisis Metodologi Tafwīḍ dalam Kitab al-Ṣifāt - Muhammad Habib Yusra; Reza Reza; Ahmad Fadlan Al Jabbar; M. Farid Zaini (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2025)
The theological orientation of al-Dāruquṭnī concerning the ḥadīths of divine attributes has long been a subject of scholarly debate, with competing interpretations placing him within either the Ashʿarī or Salafī theological tradition. This study aims to examine al-Dāruquṭnī’s methodology in understanding the ḥadīths of divine attributes in Kitāb al-Ṣifāt and to clarify his theological orientation through a systematic textual analysis. Employing a qualitative approach with content analysis, the study uses Kitāb al-Ṣifāt as the primary source, supported by classical works, contemporary scholarship, and relevant academic studies. The findings reveal that al-Dāruquṭnī consistently adopts a transmission-oriented methodology by preserving both the isnād and matn, transmitting identical reports through multiple chains to strengthen their authority, and citing early scholars as normative references for understanding these traditions. He rejects speculative interpretation, avoids anthropomorphism (tashbīh), and advocates accepting the traditions without inquiring into their ultimate reality (bilā kayf). These characteristics suggest that his approach is more closely aligned with tafwīḍ al-maʿnā, reflecting the theological tendencies of the early Ashʿarī tradition, rather than tafwīḍ al-kaifiyyah commonly associated with contemporary Salafī thought. This study contributes to a clearer understanding of al-Dāruquṭnī’s theological position and enriches contemporary discussions on ḥadīth methodology and Islamic theology.